2011
DOI: 10.1016/j.bbamem.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics and dynamics of triglyceride-phospholipid model membranes: Implications for cellular properties and function

Abstract: We demonstrate here that triolein alters the mechanical properties of phospholipid membranes and induces extraordinary conformational dynamics. Triolein containing membranes exhibit fluctuations up to size range of 100μm and with the help of these are e.g. able to squeeze through narrow passages between neighbouring structures. Triolein-phosphatidylcholine membranes were found to have bending rigidity significantly lower than that of corresponding pure phosphatidylcholine membrane. Moreover, the triolein conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…Finally, we determined the bending rigidity (K) by nanotube pulling experiments (Figure 4D and S4E-I). We found that the presence of triolein in a PC GUV bilayer decreased the bending rigidity (12 ± 4 kBT) roughly by a factor of two compared to the value for a bare GUV (21 ± 4 kBT) (Figure 4E); a similar trend was found when measuring the rigidity by fluctuation analysis (42). Surprisingly, squalene slightly increased the bending rigidity (27 ± kBT), illustrating that oil molecules do not necessarily change membrane properties in the same way.…”
Section: Oil Molecules Modify the Mechanical Properties Of A Bilayersupporting
confidence: 79%
“…Finally, we determined the bending rigidity (K) by nanotube pulling experiments (Figure 4D and S4E-I). We found that the presence of triolein in a PC GUV bilayer decreased the bending rigidity (12 ± 4 kBT) roughly by a factor of two compared to the value for a bare GUV (21 ± 4 kBT) (Figure 4E); a similar trend was found when measuring the rigidity by fluctuation analysis (42). Surprisingly, squalene slightly increased the bending rigidity (27 ± kBT), illustrating that oil molecules do not necessarily change membrane properties in the same way.…”
Section: Oil Molecules Modify the Mechanical Properties Of A Bilayersupporting
confidence: 79%
“…Lipoprotein oxidation promotes the linkage between fatty acids reducing the mobility of the chains which increases the rigidity of the lipid monolayer . In turn, the fluidity of the HDL monolayer influences ApoA‐I conformation and binding to HDL . Thus, a close interrelationship exists between HDL oxidative status, ApoA‐I, and HDL fluidity, the three main factors which appear related to CEC in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Similar to PL results, the omega-6:omega-3 ratio increased, as well as that in arachidonic acid. Despite TGs major role to provide energy, their compositional modifications were linked to alterations in the physical properties of cellular membranes [45]. The main reason behind this is that they are incorporated into the lipid bilayer and assist the maintenance of cell membranes.…”
Section: Discussionmentioning
confidence: 99%